Overexpression of Plastid Transketolase in Tobacco Results in a Thiamine Auxotrophic Phenotype. Issue 2 (10th February 2015) - Khozaei, Mahdi; Fisk, Stuart; Lawson, Tracy; Gibon, Yves; Sulpice, Ronan; Stitt, Mark; Lefebvre, Stephane C.; Raines, Christine A.
Abstract : An unexpected phenotype caused by overexpression of the plastid transketolase enzyme provides evidence that transketolase activity is an important determinant of thiamine availability in the plant. Abstract: To investigate the effect of increased plastid transketolase on photosynthetic capacity and growth, tobacco ( Nicotiana tabacum ) plants with increased levels of transketolase protein were produced. This was achieved using a cassette composed of a full-length Arabidopsis thaliana transketolase cDNA under the control of the cauliflower mosaic virus 35S promoter. The results revealed a major and unexpected effect of plastid transketolase overexpression as the transgenic tobacco plants exhibited a slow-growth phenotype and chlorotic phenotype. These phenotypes were complemented by germinating the seeds of transketolase-overexpressing lines in media containing either thiamine pyrophosphate or thiamine. Thiamine levels in the seeds and cotyledons were lower in transketolase-overexpressing lines than in wild-type plants. When transketolase-overexpressing plants were supplemented with thiamine or thiamine pyrophosphate throughout the life cycle, they grew normally and the seed produced from these plants generated plants that did not have a growth or chlorotic phenotype. Our results reveal the crucial importance of the level of transketolase activity to provide the precursor for synthesis of intermediates and to enable plants to produce thiamine and thiamine pyrophosphate for growth and development. The mechanism determining transketolase protein levels remains to be elucidated, but the data presented provide evidence that this may contribute to the complex regulatory mechanisms maintaining thiamine homeostasis in plants.